2007
DOI: 10.1111/j.1467-6486.2006.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

Contract Law and the Governance of Inter‐Firm Technology Partnerships – An Analysis of Different Modes of Partnering and Their Contractual Implications*

Abstract: This paper studies some major legal implications of inter-firm technology partnering through equity joint ventures, non-equity partnerships, and licensing contracts. These different partnerships are placed within the classical and relational contracting perspectives, while also considering intellectual property rights issues. Samples of contracts of partnerships in bioscience, fine chemicals, biotechnology and biopharmaceuticals are analysed, in detail, with reference to the distribution of property rights, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
126
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 57 publications
2
126
0
1
Order By: Relevance
“…This strategy is much more in line with what could be expected according to wellaccepted organizational economics theory (e.g. Williamson, 1985) that is closer to Chesbrough (2006a,b) than to a more 'radical' open innovation approach, as advocated by Baldwin andvon Hippel (2011), von Hippel andvon Krogh (2006) and Pénin (2011 (Almirall and Casadesus-Masanell, 2010;Hagedoorn and Hesen, 2007;Lee, Nystén-Haarala, and Huhtilaienen, 2010). Also, both the control and the monitoring dimension of contracts, the degree to which firms use contracts from a legal or from a practical process perspective, appear to be relevant for open innovation collaboration.…”
Section: Discussionsupporting
confidence: 64%
“…This strategy is much more in line with what could be expected according to wellaccepted organizational economics theory (e.g. Williamson, 1985) that is closer to Chesbrough (2006a,b) than to a more 'radical' open innovation approach, as advocated by Baldwin andvon Hippel (2011), von Hippel andvon Krogh (2006) and Pénin (2011 (Almirall and Casadesus-Masanell, 2010;Hagedoorn and Hesen, 2007;Lee, Nystén-Haarala, and Huhtilaienen, 2010). Also, both the control and the monitoring dimension of contracts, the degree to which firms use contracts from a legal or from a practical process perspective, appear to be relevant for open innovation collaboration.…”
Section: Discussionsupporting
confidence: 64%
“…However, no matter how specified licensing contracts are drafted, they still contain some element of uncertainty. Therefore, even though licensing agreements are clearly less relational than many other forms of inter-firm cooperation, they are still to some degree incomplete contracts as not all contingencies of future and broader use can be foreseen (Hill, 1992;Bessy and Brousseau, 1998;Hagedoorn and Hesen, 2007).…”
Section: H1mentioning
confidence: 99%
“…Managerial autonomy can influence the acquired firm's intention to leave or stay. Hagedoorn and Hesen (2007) observed that managers with greater managerial discretion tend to be highly motivated and expend additional effort in pursuit of their strategic goals. The degree of autonomy given to the acquired firm increases the relative decision-making latitude of acquired managers' and employees.…”
Section: Autonomy Financial Incentives and Employee Retentionmentioning
confidence: 99%